Bio-prospecting of coral (Porites lutea) mucus associated bacteria, Palk Bay reefs, Southeast coast of India. (December 2017) - Ahila, N.K.; Prakash, S.; Manikandan, B.; Ravindran, J.; Prabhu, N.M.; Kannapiran, E.
Abstract: Coral mucus is one of the key localization in the coral holobiont, as this serves as an energy rich substrate for a wide range of abundant, diverse and multifunctional microbiota. However, very little is known about the functional role of bacterial communities in their associations with corals. In the present study, a total of 48 isolates were obtained from Porites lutea wherein the genus of Bacillus sp. and Vibrio sp. were predominant. Bio-prospecting the coral mucus revealed the existence of (10.42%) antagonistic bacteria against the tested bacterial pathogens. Molecular taxonomy (16S rRNA) proved the identity of these antagonistic bacteria belong to Enterobacter cloacae (CM1), Bacillus subtilis (CM2), Bacillus sp. (CM11) and Bacillus marisflavi (CM12). The secondary screening emphasized that the ethyl acetate extract of B. subtilis showed strong antagonistic effect, followed by the chloroform extract of E. cloacae and ethyl acetate extract of B. marisflavi . The antagonistic activity was statistically confirmed by Principal Component Analysis and Hierarchical Cluster Analysis. The privileged coral mucus associated bacterial (CMAB) solvent extracts inhibited the bacterial pathogens at 100 μg/ml (MIC) and ceased the growth at 200 μg/ml (MBC). The hemolytic and brine shrimp lethality assays disclosed the non-toxic nature of solvent extracts of CMAB. Altogether, the present investigation brought out the diversity of bacteria associated with the mucus of P. lutea . In addition, bio-prospecting corroborated the CMAB as the potential source of pharmacologically important bioactive compounds against a wide range of bacterial pathogens. Highlights: Enumeration, Isolation and Phenotypic identification of bacteria consociated with the mucus of coral, P. lutea. Coral mucus associated bacteria screened for its antagonistic activity against 13 bacterial pathogens. Molecular identification revealed that the Bacillus sp. were the dominant combaters among the antagonistic coral mucus associated bacteria. Effective antagonistic activity, bio-compatible and less-toxic.